PENGEMBANGAN MEDIA PEMBELAJARAN IPAS BERBASIS LITERASI SAINS PADA MATERI SISTEM PENCERNAAN UNTUK SISWA DI SDI PEMANA - Leneng, Lusia; Dinatha, Ngurah Mahendra; Dolo, Fransiskus Xaverius; Kua, Maria Yuliana (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study aims to describe the science learning media based on scientific literacy on the simple respiratory system material at SDI Pemana. The low scientific literacy at SDI Pemana causes students to be less responsive to developments and problems that occur in the surrounding environment, especially those related to natural phenomena. The type of research used in this study is the ADDIE research and development model which consists of five stages, namely (Analysis, Design, Development, Implementation, Evaluation). The subjects in this study were 30 fifth grade students. The sample in this study was taken as a total sample (total sampling), where all fifth grade students were used as respondents in the trial of science literacy-based science learning media. The results of the study conducted at SDI Pemana showed that science literacy-based science learning media on the digestive system material was very feasible to be used in science learning. The feasibility of this product was analyzed through a validation process by material experts and media experts, and reinforced by the results of field trials that showed a positive response from students and teachers to the use of the media in learning activities. Based on the research conducted related to the development of science learning media based on scientific literacy on simple respiratory system material at SDI Pemana which has been carried out, it can be concluded that the development of this learning media has been successful and very useful in improving students' scientific literacy at SDI Pemana